Global significance of extensive grazing lands and pastoral societies: An introduction - Reid, Robin S.; Galvin, K.A.; Kruska, R.S. (Springer, 2008)
More of the land surface of the earth is used for grazing than for any other purpose (FAO 1999, WRI 2000, Asner et al. 2004, Ojima and Chuluun, Chapter 8). Although livestock and wildlife graze in forests and woodlands, we focus here on the lands where most herding peoples and their livestock graze: in ‘open’ grazing lands, which include savannas, grasslands, prairies, steppe, and shrublands (Asner et al. 2004). These grazing lands cover 61.2 million km2 or 45% of the earth’s surface (excluding Antarctica), 1.5 times more of the globe than forest, 2.8 times more than cropland and 17 times more than urban settlements (see Figure 1-1)2. These lands range from extremely dry (hyper-arid) to very wet (humid) and represent 78% of the land area grazed by livestock (Asner et al. 2004).